2017
DOI: 10.1007/s11356-017-8615-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice towards ergonomics among undergraduates of Faculty of Dentistry, Tanta University, Egypt

Abstract: Ergonomics is the scientific study of people and their working environment. Dentistry is a profession that generally produces various musculoskeletal disorders. If ergonomic principles are applied in the field of dentistry, it helps to prevent occupational ergonomic health hazards and provides more comfort to the dentist and patient. To assess knowledge, attitudes, and practice of ergonomics during routine dental procedures among undergraduates of Faculty of Dentistry, Tanta University, cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
1
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 12 publications
8
40
1
16
Order By: Relevance
“…According to the results of the present study all the dentists approved that dental chair and instruments play major role in adopting ergonomics' principles, this disagrees with El-Sallamy et al; 2017 who revealed that only 56.4% thought that dental chair and instruments play a role in adopting ergonomics during dental work (17) . More than half of the studied sample (67.5%) knew the ideal sitting angle, while 72.5% didn't know the depth of chair, 65% didn't know the ideal sitting posture, more than half (60%) of the interns didn't know the ideal position of the patient, and 82.5% didn't know the ideal distance between the dentist and the instruments, these results disagree with Barlean et al; 2012 and Madaan and Chaudhari; 2012, who revealed that half of the dentists had fair knowledge (20,21) , this could be attributed to lack of ergonomics principles in our curricula.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…According to the results of the present study all the dentists approved that dental chair and instruments play major role in adopting ergonomics' principles, this disagrees with El-Sallamy et al; 2017 who revealed that only 56.4% thought that dental chair and instruments play a role in adopting ergonomics during dental work (17) . More than half of the studied sample (67.5%) knew the ideal sitting angle, while 72.5% didn't know the depth of chair, 65% didn't know the ideal sitting posture, more than half (60%) of the interns didn't know the ideal position of the patient, and 82.5% didn't know the ideal distance between the dentist and the instruments, these results disagree with Barlean et al; 2012 and Madaan and Chaudhari; 2012, who revealed that half of the dentists had fair knowledge (20,21) , this could be attributed to lack of ergonomics principles in our curricula.…”
Section: Discussioncontrasting
confidence: 96%
“…According to the results of the current study it was found that high percentage of interns (95%) believed in the importance of the concepts of ergonomics, this goes in agreement with Mailoa & Rovani 2011 (19) and El-Sallamy et al; 2017 (17) , this may be due to receiving information about ergonomics from internet and supervisors during clinical work, on the contrary these results disagree with results of study conducted by Madaan and Chaudhari 2012, which showed lower scores of awareness (19%) (20) . In addition, 87.5% accepted to follow ergonomics during routine dental work, referring to its importance in reducing pain and fatigue.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations